Inhibitory Mechanisms in Primary Somatosensory Cortex Mediate the Effects of Peripheral Electrical Stimulation on Tactile Spatial Discrimination - Saito, Kei; Otsuru, Naofumi; Inukai, Yasuto; Kojima, Sho; Miyaguchi, Shota; Tsuiki, Shota; Sasaki, Ryoki; Onishi, Hideaki (Neuroscience, 2018)
•High-intensity PES was effective in improving GOT when the subjects had low GOT performance at baseline.•Improving GOT performance by high-intensity PES was related to reduction in N20_SEP-PPD in the low GOT performance group.•High-intensity PES decreased N20 SEP-PPD in the GOT improvement group but increased N20_SEP-PPD in the GOT decrement group. Selective afferent activation can be used to improve somatosensory function, possibly by altering cortical inhibitory circuit activity. Peripheral electrical stimulation (PES) is widely used to induce selective afferent activation, and its effect may depend on PES intensity. Therefore, we investigated the effects of high- and low-intensity PES applied to the right index finger on tactile discrimination performance and cortical somatosensory-evoked potential paired-pulse depression (SEP-PPD) in 25 neurologically healthy subjects. In Experiment 1, a grating orientation task (GOT) was performed before and immediately after local high- and low-intensity PES (both delivered as 1-s, 20-Hz trains of 0.2-ms electrical pulses at 5-s intervals). In Experiment 2, PPD of SEP components N20/P25_SEP-PPD, N20_SEP-PPD and P25_SEP-PPD, respectively, were assessed before and immediately after high- and low-intensity PES. Improved GOT discrimination performance after high-intensity PES (reduced discrimination threshold) was associated with lower baseline performance (higher baseline discrimination threshold). Subjects were classified into low and high (baseline) GOT performance groups. Improved GOT discrimination performance in the low GOT performance group was significantly associated with a greater N20_SEP-PPD decrease (weaker PPD). Subjects were also classified into GOT improvement and GOT decrement groups. High-intensity PES decreased N20_SEP-PPD in the GOT improvement group but increased N20_SEP-PPD in the GOT decrement group. Furthermore, a greater decrease in GOT discrimination threshold was significantly associated with a greater N20_SEP-PPD decrease in the GOT improvement group. These results suggest that high-intensity PES can improve somatosensory perception in subjects with low baseline function by modulating cortical inhibitory circuits in primary somatosensory cortex.